Assessment of histopathological features of maculopapular viral exanthem and drug‐induced exanthem. (13th October 2017) - Singh, Sanjay; Khandpur, Sujay; Arava, Sudheer; Rath, Ramashankar; Ramam, M.; Singh, Manoj; Sharma, Vinod K.; Kabra, Sushil Kumar
Abstract : Background: Viral infections and drug reactions are the commonest causes of exanthems in clinical practice. Clinically, their overlapping features may pose a diagnostic challenge. Hematologic, in vitro, and drug provocation tests are either unreliable or impractical. Methods: This was a descriptive, prospective study to assess and compare histopathological features of maculopapular viral and drug exanthem. Subjects fulfilling case definition of exanthems were included. Serum C‐reactive protein (CRP) and absolute eosinophil count (AEC) were also studied. Results: Skin biopsy slides of 48 cases were evaluated and AEC and CRP were performed. Both median AEC and CRP were lower in viral exanthem compared with drug exanthem. On histopathological evaluation, features such as lymphocytic exocytosis, and dermal infiltrate of eosinophils, lymphocytes and histiocytes were seen in a significantly greater number of drug exanthems. Other findings such as focal spongiosis, acanthosis, keratinocyte necrosis, basal cell damage, papillary dermal edema and atypical lymphocytes in the dermis were also observed in higher though not statistically significant number of drug exanthem biopsies. Conclusions: Certain histopathological features can help to differentiate between the two exanthems and this modality may be used in situations when there is clinical overlap and when drug rechallenge cannot be undertaken.